Comunicação integrada de marketing em redes de farmácias. - Silva, Antonio Marcos Alcântara da (2011)
Communication is a key component of the marketing and contributes decisively to success of any company. The aim for integrating marketing communications is their competitive advantage for businesses. However, many companies are not aware of this and has not invested enough resources to transform the Integrated Marketing Communications (IMC) into a contribution not only strategic but tactical. To the pharmacy network, there aren't differences. The aim of this paper was to determine if the communication on the pharmacy network at the city of Maringá is characterized as Integrated Marketing Communications. Data were collected with application of a survey and analyzed using nonparametric tests with aid of the SPSS software. According to results, it was possible to verify that the majority of the Maringá pharmacy network has developed some form of marketing communication during the sample period. However, the marketing communication of the promotional advertising of these companies has not been characterized as the IMC. Therefore, among the pharmacy network investigated there is just a significant association between the importance and effort for performing the following communication tools of marketing: digital marketing, direct marketing and sponsorship. There was no significant correlation between emphasis and effort devoted to the following tools: advertising, personal selling, publicity, public relations and sales promotion. It was identified that the lack of investment in developing human resources with specialized skills is a major obstacle to the adoption of the CIM in the companies surveyed. Even though the results were encouraging in terms of willingness to communicate marketing managers to implement integrated communication programs yet, it was not possible to characterize the marketing communication network of pharmacies at the city of Maringá as IMC.